Ticks (Acari: Ixodidae) associated with small terrestrial mammals in the state of Minas Gerais, southeastern Brazil - Saraiva, Danilo G. (2012)
From June 2005 to November 2010, 43 small mammals encompassing 6 species of Didelphimorphia, 8 species of Rodentia, and 1 species of Lagomorpha were found parasitized by ticks in the state of Minas Gerais, southeastern Brazil. Nine tick species, in total 186 specimens, were identified as follows: Amblyomma cajennense (larvae and nymphs) on opossums and rodents; Amblyomma ovale (nymphs) on rodents; Amblyomma parvum (nymphs) on rodents; Amblyomma coelebs (nymphs) on opossums; Amblyomma dubitatum (nymph) on opossums; Ixodes amarali (females, nymphs, and larvae) on opossums and rodents; Ixodes loricatus (male, females, nymph) on opossums; Ixodes schulzei (female) on rodents; and Haemaphysalis leporispalustris (female) on rabbits. Most of the tick-host associations found in the present study have never been recorded in the literature; those include three new host records for I. amarali, four for A. cajennense, one for A. dubitatum, two for A. ovale, and one for A. coelebs. In addition, we provide the first record of A. coelebs in the state of Minas Gerais.